Digitalização de substituição: análise do decreto nº 10.278/2020 e da produção do representante digital - Dalton Garcia do Carmo (2023)
The replacement digitization granted the digital representative the same legal value as the original paper archival document, provided that the attributes presented in Decree No. 10.278/2020 were met. Subsequently, National Archives Council Resolution No. 48 and the Brazilian Association of Technical Standards standard - Recommended Practice 1.013 were published, with the aim of guiding the process for producing the digital representative in institutions. The general objective defined was to parameterize the production of the digital representative with criteria that guarantee the presumption of authenticity for the digital representative, based on an analysis of the aforementioned publications and research into archival literature in the digital context. The specific objectives were: the conceptualization of the attributes presented in the decree, the theoretical foundation of the replacement digitization procedures according to the bibliographies consulted and the systematization of actions necessary for the production of the digital representative. In this way, it was possible to establish the flow for digitization, the good practices for guaranteeing the quality of the process, the preparation of the digital environment for inserting the digital document, electronic authentication and the properties of the digital file format, the backing and legal value for the digital representative. The qualitative and exploratory approach, as well as bibliographic and documentary research, allowed for broad coverage, in a variety of sources, and investigation of the topic. As a result, from the survey of proposals, laws and decrees, it was observed that the digitization of replacement has been on the legislative agenda for decades. In turn, the archival community has carried out research and criticized government initiatives based on scientific knowledge. The importance of archival standards for digitization procedures was noted, in order to guarantee the preservation of documents. Institutions and civil society are in the midst of Digital Transformation and technological tools can help improve access, retrieval and preservation of information. However, it was confirmed that document management, regardless of whether the documentary support is digital or non-digital, brings together the necessary mechanisms to preserve the digital representative. Finally, the actions and aspects necessary in the environment for the digitization of replacement, in the governmental, institutional and professional spheres, which need to be considered in the production of the digital representative, were presented.